PENYULUHAN IMUNISASI DASAR LENGKAP PADA IBU BADUTA DI DESA ATEUK LAMPHANG - Safrizal; Ulfa, Mutia; Suhariati, Nadia; Margfirah; Depari, Desli Lonika Br; Aulia, Tazkiyatul (Universitas Aufa Royhan Di Kota Padangsidipuan, 2025)
A reduction in vulnerability to contagious diseases among babies and toddlers had resulted from undergoing the full program of core vaccinations. However, in Ateuk Lamphang Village, the coverage of complete basic immunization remains very low, partly due to mothers’ limited knowledge and concerns about Adverse Events Following Immunization (AEFI). Improvement in maternal understanding regarding immunization for children under two had been evaluated in this community program to see how effective the counseling was. The counseling activity was carried out interactively using posters and PowerPoint slides, involving 11 mothers as participants through total sampling. Initial and concluding tests had provided the basis for evaluation, and the data were further interpreted using the McNemar statistical technique. The results showed an increase in knowledge, where prior to counseling most mothers had low knowledge (63,6%) and only 36,4% had good knowledge. After the counseling, the proportion of mothers with good knowledge increased to 90,9%, while those with low knowledge decreased to 9,1%. The McNemar test indicated a p-value of 0,031 (p < 0,05), meaning there was a certain significance differences in mothers’ knowledge before and after counseling. It can be concluded that counseling on complete basic immunization is effective in improving the knowledge of mothers with children under two years old in Ateuk Lamphang Village.